Neo-Marxism as a Foundation of Radical Educational Theory (Part II). Henry Giroux?s Revisions of Marxism for the Philosophy of Education - Kruszelnicki, Wojciech (INSTED: Interdisciplinary Studies in Education & Society, 2016)
This paper represents the second installment of the article entitled Neo-Marxism as a Foundation of Radical Educational Theory. Its aim is to supplement the intellectual history of neo-Marxism in educational theory with the critique of its basic assumptions and conceptions offered by Henry Giroux. Following H. Giroux, I analyze the theoretical insights and weaknesses of neo-Marxist theories of reproduction, while attempting to pinpoint certain shortcomings of H. Giroux?s own critique of authors such as P. Bourdieu, S. Bowles and H. Gintis, L. Althusser, P. Willis, and others. I then reconstruct H. Giroux?s revision of the basic categories of classical Marxism (reproduction, culture, ideology), and show the possibilities of their reinterpretation and radicalization within a critical pedagogy aiming at social reconstruction and emancipation.